The Pioneering Applications of Generative AI - Kumar, Raghvendra, 1987-; Sahu, Sandipan, 1981-; Bhattacharya, Sudipta, 1981- (Hershey, PA, USA : IGI Global, Engineering Science Reference (an imprint of IGI Global), 2024)
"This book focused on teaching readers how to implement generative AI techniques using the Python programming language. It cover topics such as generative adversarial networks (GANs), variational autoencoders (VAEs), and other methods for creating AI systems that can generate new content, such as images, text, or music"--
Prof. Madya Ts. Dr. Hasyiya Karimah Binti Adli
Includes bibliographical references and index.
Keywords: Machine learning; Artificial intelligence; Python (Computer program language)